Traditional Strategies and AI-Integrated Strategies in Learning English among EFL Omani Students - Jomaa, Nayef; Mudhsh, Badri Abdulhakim; AlGhafri, Khalid (Jurnal Arbitrer (Online), 2025)
This study examines the impact of gender and academic levels on using both traditional and AI-integrated learning strategies among EFL Omani students. This quantitative study utilized a questionnaire with a five-point Likert scale based on Oxford’s Strategy Inventory for Language Learning (SILL) and other AI-related items adapted from current studies, including 152 students from a public Omani university. The research instrument was expert-reviewed, followed by a pilot study, and the main data were analyzed using SPSS, namely t-tests and ANOVA. Out of 35 question items related to traditional learning strategies, Omani female learners outperformed male students in 26 items, significantly in writing new words (F= 4.00, M= 3.63), online English classes (F= 3.36, M= 2.99), practice grammar (F= 3.56, M= 3.01), and learn pronunciation (F= 4.44, M= 3.78). Similarly, Omani female learners outperformed male learners in all nine AI-based strategies, namely AI tools to enhance speaking (F= 3.44, M= 3.15), learn pronunciation (F= 3.54, M= 3.19), and improve writing (F= 3.43, M= 3.25). Students’ academic levels also affected some strategies like listening, speaking, and pronunciation; higher-level students preferred interactive approaches related to AI compared with lower-level students. However, AI tools for learning grammar and writing were less commonly used. These findings suggest that integrating traditional and AI-assisted strategies could support learning foreign languages. Consequently, educators should encourage active engagement in AI-based learning while addressing students’ dependence on traditional strategies.